Chemical Content and Antibacterial Activity of Some Extracts of Anastatica hierochuntica leaves - AL-Saeed , Arwa (University of Thi-Qar Journal of Science, 2013)
The present study was undertaken to study the chemical content and antibacterial activity of Anastatica hierochuntica leaves by preparation extracts (n-hexan, ethanolic 70% and aqueous) and tested against Grampositive bacteria (Streptococcus pyogens and Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa and Proteus vulgaris). The results of chemical analysis showed that hexan extract contains phenols , terpenes and sterols only, while extracts (ethanolic 70% and aqueous) contain carbohydrates , phenols , flavonoids , tannins , saponins and alkaloids also observed contained this plant on minerals (Cu, Zn and Fe ) in concentrations (8.65±0.30, 47.51±1.31, 169.48±7.11) ppm respectively.The antibacterial activity of the preparation extracts was evaluated using agar well-diffusion method, the results indicated that plant extracts were more active against Gram-negative bacteria than Gram-positive  bacteria, alcoholic extract has antibacterial activity stronger than hexan and aqueous extracts. From this results we concluded that Anastatica hierochuntica leaves can used in treatment of various disorders by havea number of active components and antibacterial activity.